2013
DOI: 10.1111/ldrp.12001
|View full text |Cite
|
Sign up to set email alerts
|

Reaching the Mountaintop: Addressing the Common Core Standards in Mathematics for Students with Mathematics Difficulties

Abstract: The Common Core State Standards provide teachers with a framework of necessary mathematics skills across grades K‐12, which vary considerably from previous mathematics standards. In this article, we discuss concerns about the implications of the Common Core for students with mathematics difficulties (MD), given that students with MD, by definition, struggle with mathematical skills. We suggest that instruction centered on the Common Core will be challenging and may lead to problematic outcomes for this populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 73 publications
2
68
0
Order By: Relevance
“…However, teaching procedures without concepts likely leaves students confused and unable to judge the accuracy of their answers (Kilpatrick et al, 2001; Rittle-Johnson & Siegler, 1998), as both conceptual and procedural knowledge are important for developing an understanding of fraction magnitude (e.g., Rittle-Johnson, Siegler, & Alibali, 2001). This is especially true for students with risk for mathematics difficulties, since these students struggle with foundational mathematics skills such as addition and multiplication (e.g., Powell et al, 2013). When students lack both procedural competence and conceptual knowledge, understanding fraction principles becomes substantially difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, teaching procedures without concepts likely leaves students confused and unable to judge the accuracy of their answers (Kilpatrick et al, 2001; Rittle-Johnson & Siegler, 1998), as both conceptual and procedural knowledge are important for developing an understanding of fraction magnitude (e.g., Rittle-Johnson, Siegler, & Alibali, 2001). This is especially true for students with risk for mathematics difficulties, since these students struggle with foundational mathematics skills such as addition and multiplication (e.g., Powell et al, 2013). When students lack both procedural competence and conceptual knowledge, understanding fraction principles becomes substantially difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This expectation is based on findings by Fuchs, Fuchs et al (2015), who found that, across three years of intervention research, the achievement gap on fractions performance widened between at-risk students and their not-at-risk classmates in the same district where the present study took place moved toward implementation of CCSS. This widening gap is likely due to the rigor of CCSS, affording greater learning outcomes for not-at-risk students, even as it posed specific difficulty for at-risk students who already struggle with foundational skills (Powell, Fuchs, & Fuchs, 2013). Specifically, low performing students tend to struggle with magnitude estimation (e.g., Fuchs et al, 2013; Fuchs, Fuchs et al, 2015; Mazzocco & Devlin, 2008), a core tenet of fraction learning outlined in the CCSS.…”
Section: The Present Studymentioning
confidence: 99%
“…The dynamics of learning is in evidence here: practice the basic procedure, apply the procedure with multiple mistakes, try again and make fewer and different mistakes, and then reach proficiency (Powell, Fuchs, & Fuchs, 2013;VanDer Heyden & Allsopp, 2014).…”
Section: Essential Component-epa Strategymentioning
confidence: 99%
“…Help preservice educators learn how to identify students who warrant early intervention using diagnostic tools, such as formal progress monitoring measures (e.g., Lembke & Foegen, 2009) or standardized measures (e.g., KeyMath; Connolly, 2007). • • Review learning trajectories of students with mathematics difficulty and how to reinforce foundational mathematics skills while working toward general curriculum goals (Powell, Fuchs, & Fuchs, 2013). • • Highlight cognitive strategies that help students with comorbid disabilities complete mathematics work while controlling for other disabilities.…”
Section: How To Address This Key Element?mentioning
confidence: 99%